2019
DOI: 10.3847/2041-8213/ab5226
|View full text |Cite
|
Sign up to set email alerts
|

Two Years of Nonthermal Emission from the Binary Neutron Star Merger GW170817: Rapid Fading of the Jet Afterglow and First Constraints on the Kilonova Fastest Ejecta

Abstract: We present Chandra and VLA observations of GW 170817 at ∼ 521−743 days post merger, and a homogeneous analysis of the entire Chandra dataset. We find that the late-time non-thermal emission follows the expected evolution of an off-axis relativistic jet, with a steep temporal decay F ν ∝ t −1.95±0.15 and power-law spectrum F ν ∝ ν −0.575±0.007 . We present a new method to constrain the merger environment density based on diffuse Xray emission from hot plasma in the host galaxy and find n ≤ 9.6×10 −3 cm −3 . Thi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

19
138
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 170 publications
(159 citation statements)
references
References 70 publications
19
138
1
1
Order By: Relevance
“…Within the associated uncertainties, these results are consistent with the broadband evolution of AT 2017gfo (e.g. Alexander et al 2018;Lamb et al 2019;Troja et al 2019;Hajela et al 2019).…”
supporting
confidence: 88%
See 1 more Smart Citation
“…Within the associated uncertainties, these results are consistent with the broadband evolution of AT 2017gfo (e.g. Alexander et al 2018;Lamb et al 2019;Troja et al 2019;Hajela et al 2019).…”
supporting
confidence: 88%
“…The fitted radio spectral index α 1 from this study is −0.53 ± 0.04, consistent with broadband spectral indices determined using radio, optical and X-ray data at various epochs, where the typical value is approximately −0.58 (e.g. Margutti et al 2018;Troja et al 2018Troja et al , 2019Alexander et al 2018;Hajela et al 2019). Mooley et al (2018c) also found power-law dependencies for the rise and decay phases of approximately t 0.8 and t −2.4 , respectively, where t is the time since the merger.…”
supporting
confidence: 87%
“…We calculate the medians for the parameters, = (Figure 4). Motivated by the low value of ò B ≈10 −4 -10 −2 derived for GW170817ʼs afterglow (e.g., Wu & MacFadyen 2018;Hajela et al 2019), as well as those derived for Swift SGRBs (Santana et al 2014;Zhang et al 2015), we explore the possibility of a low value of ò B and find that the allowed parameter space is completely ruled out for ò B 10 −3 (for ò e =0.1). In summary, we derive E K,iso ≈0.13-0.14×10 52 erg and n≈0.04-1.10 cm −3 for GRB 181123B.…”
Section: Afterglow Propertiesmentioning
confidence: 96%
“…An X-ray signal (Troja et al 2017;Margutti et al 2017;Haggard et al 2017;Ruan et al 2018;Pooley et al 2017) and a radio signal (Hallinan et al 2017;Alexander et al 2017;Mooley et al 2018) were discovered at the position of the optical transient after $ 9 days and $ 16 days, respectively. A slow multi-wavelength flux-rise of the non-thermal emission was observed until $ 150 days (Lyman et al 2018;Margutti et al 2018;Troja et al 2018) before entering a flattening-decaying phase (D'Avanzo et al 2018;Dobie et al 2018;Alexander et al 2018;Hajela et al 2019;Fong et al 2019). Very Long Baseline Interferometry observations enabled measurement of the superluminal proper motion of the radio counterpart (Mooley et al 2018) and constrained the apparent size of the source (Ghirlanda et al 2019), proving that a relativistic and narrowlycollimated jet successfully emerged from the neutron star merger.…”
Section: The O1 and O2 Follow-up Programmentioning
confidence: 99%